Implementation of green practices to improve the brand image of Nandini Jungle Resort & SPA Bali - I Ketut Milena Rida Artha; I Gusti Agung Bagus Mataram; Elvira Septevany (Journal of Applied Sciences in Travel and Hospitality, 2023)
This study discusses an environmentally friendly approach to determine whether implementing green practices can improve the brand image of Nandini Jungle Resort & Spa in the consumer’s mind. The data collection was obtained through observations, questionnaires, and interviews. This study refers to the Likert scale, where each statement uses 1-5 scaled categories answers. Purposive sampling with 100 samples is used as the sampling technique. Simple linear regression is used as a quantitative analysis technique. This research concluded that there is a positive and significant effect on the implementation of green practices variable to the brand image enhancement variable. Calculated using a statistical formula using special software for data analysis from International Business Machine (IBM) Corporation called Statistical Package for the Social Sciences (SPSS) Version 25. The statistical calculation results of the analysis indicate that the variance or the value of Adjusted R Square is 0.701. Therefore, it can be concluded that the influence of green practices implementation (X) on brand image improvement (Y) is 70.1%. It means that green practices can affect the brand hotel.